2021
DOI: 10.3920/jiff2020.0105
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of spent mushroom substrate and food waste: utilisation as feed materials for black soldier fly (Hermetia illucens (L.) Diptera: Stratiomyidae)

Abstract: Spent mushroom substrate (SMS) is the organic material remaining after harvesting mushrooms. We evaluated the potential of using SMSs of four different edible fungi (Auricularia heimuer, Lentinus edodes, Pleurotus eryngii and Pleurotus citrinopileatus) as a food resource for rearing black soldier fly (Hermetia illucens) larvae (BSFL) and to decrease waste recycling and save conventional feed. The larval weight after being fed only on the SMS of L. edodes (68.8 mg), a mushroom with worldwide cultivation, was he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The group of restaurant waste that contained no pure sediment demonstrated the lowest BSFL survival rate, while the group of restaurant waste that had meat sediment showed a higher BSFL survival rate (Figure 2). This corroborates the previous finding by Li et al (2021). Adding restaurant waste to the substrate for BSFL culture to improve the survival rate of BSFL is not a very rare occurrence and has been used before (Cai et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The group of restaurant waste that contained no pure sediment demonstrated the lowest BSFL survival rate, while the group of restaurant waste that had meat sediment showed a higher BSFL survival rate (Figure 2). This corroborates the previous finding by Li et al (2021). Adding restaurant waste to the substrate for BSFL culture to improve the survival rate of BSFL is not a very rare occurrence and has been used before (Cai et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Both the average insect length and insect weight showed a remarkable difference in 100% restaurant waste and 1:4 groups than in other groups. Li et al (2021) concluded that adding 50% wheat bran, 30% alfalfa meal, and 20% corn meal resulted in an average insect length of 23.5 mm and an average insect weight of 240 mm, which were significantly different from those observed in the BSFL group fed with other pure mushroom wastes. According to Julita et al (2018), the proportion of organic waste, such as vegetables, should be increased in the substrate to improve the yield of BSFL.…”
Section: Discussionmentioning
confidence: 80%
“…The black soldier fly-derived oil is a high-quality biodiesel with a high content of medium-chain saturated fatty acids of 67% (w%) and a low concentration of polyunsaturated fatty acids of 13%. The residual serves as green compost candidates for the growth of crops ( Jucker et al, 2020 ; Li et al, 2021 ; Ragossnig and Ragossnig, 2021 ; Surendra et al, 2016 ; Zhang et al, 2021 ). Similarly, the bioconversion of swine manure using house fly provided value-added animal foodstuff with 56.9% protein and 23.8% total fat as dry matter, preventing waste products in an intensive animal production system from threatening public health ( Wang et al, 2013 ).…”
Section: Welfare and Benefits Of Edible Insect Farmingmentioning
confidence: 99%
“…The potential of six SMS derived from Auricularia cornea , Auricularia heimuer , P. eryngii , P. ostreatus , Pleurotus citrinopileatus , and L. edodes was recently evaluated to rear black soldier fly ( Hermetia illucens ) and Tenebrio molitor larvae. L. edodes SMS was shown to be the most suitable to replace the insects' conventional feed [ 96 , 97 ]. Furthermore, when Protaetia brevitarsis larvae were grown on L. edodes or Auricularia auricula-judae SMS, a nutrient-rich organic fertilizer with low phytotoxicity and high humic acid content was produced [ 98 ].…”
Section: Spent Mushroom Substrate As Feedmentioning
confidence: 99%